TG : HDL-C Ratio Is a Good Marker to Identify Children Affected by Obesity with Increased Cardiometabolic Risk and Insulin Resistance. (1st December 2019) - Nur Zati Iwani, Ahmad Kamil; Jalaludin, Muhammad Yazid; Wan Mohd Zin, Ruziana Mona; Fuziah, Md Zain; Hong, Janet Yeow Hua; Abqariyah, Yahya; Mokhtar, Abdul Halim; Wan Mohamud, Wan Nazaimoon
Abstract : Metabolic syndrome (MetS) is an important predictor of cardiovascular diseases in adulthood. This study aims to examine the clinical utility of triglyceride to high-density lipoprotein ratio (TG : HDL-C) in identifying cardiometabolic risk and insulin resistance (IR) among children with obesity, in comparison with MetS as defined by the International Diabetes Federation (IDF). Data of 232 children with obesity aged 10–16 years were obtained from our study, MyBFF@school study, conducted between January and December 2014. Children were divided into tertiles of TG : HDL-C ratio. The minimum value of the highest tertile was 1.11. Thus, elevated TG : HDL-C ratio was defined as TG : HDL-C ≥1.11. Children with MetS were categorized based on the definition established by the IDF. Out of 232 children, 23 (9.9%) had MetS, out of which 5.6% were boys. Almost twofold of boys and girls had elevated TG : HDL-C ratio compared to MetS: 13.8% vs. 5.6% and 13.8% vs. 4.3%, respectively. Children with elevated TG : HDL-C ratio had lower fasting glucose compared to children with MetS (boys = 5.15 ± 0.4 vs. 6.34 ± 2.85 mmol/l, p = 0.02 ; girls = 5.17 ± 0.28 vs. 6.8 ± 4.3 mmol/l, p = 0.03 ). Additionally, boys with elevated TG : HDL-C ratio had a higher HDL-C level compared to those with MetS (1.08 ± 0.18 vs. 0.96 ± 0.1 mmol/l, p = 0.03 ). There was no significant difference across other MetS-associated risk factors. Overall, TG : HDL-C ratio demonstrated higher sensitivity (42.7% vs. 12.9%) but lower specificity (74.8% vs. 93.2%) than MetS in identifying IR, either in HOMA-IR ≥2.6 for prepubertal children or HOMA-IR ≥4 for pubertal children. TG : HDL-C ratio in children with obesity is thus as useful as the diagnosis of MetS. It should be considered an additional component to MetS, especially as a surrogate marker for IR.